Media Representation of ‘Dark Indonesia’ 2025: A Comparative Framing Analysis of Reuters and The Jakarta Post - Muhammad Fikri Haikal Putra; Iskandar Iskandar; Sukardi Weda (Fakultas Sastra - Universitas Muslim Indonesia, 2026)
This study investigates how Reuters and The Jakarta Post framed Indonesia’s 2025 student protests, emphasizing differences in media orientation and narrative construction. Employing a qualitative descriptive approach, the analysis integrates Goffman’s (1974) concept of frame as a social schema, Entman’s (1993) four framing elements, and Semetko and Valkenburg’s (2000) five generic frames. The data were drawn from one article in each outlet, selected purposively from coverage published during the protest’s peak period in February 2025. Findings reveal that Reuters employed an event-centered and neutral tone, framing the protests primarily as a reaction to economic policy and government legitimacy. In contrast, The Jakarta Post adopted a more domestically engaged framing that emphasized democratic ideals, civic responsibility, and national identity through moral and responsibility frames. The comparative analysis reveals that institutional and editorial contexts influence media narratives, where international media tend to maintain neutrality, while domestic outlets often embed political dissent within their national discourse. This study contributes to comparative media studies by revealing how framing practices construct distinct portrayals of political activism within Southeast Asian contexts.